MARKETING COMMUNICATION STRATEGY IN ATTRACTING CONSUMER INTEREST IN THE PRODUCTS OF BANK PEREKONOMIAN RAKYAT SYARIAH AMANAH BANGSA IN SINAKSAK, SIMALUNGUN REGENCY - Miftakhul Khoiri; Ahmad Tamrin Sikumbang (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to identify marketing communication strategies in attracting consumer interest in BPRS Amanah Bangsa products in Sinaksak, Simalungun Regency using the AIDA model (Attention, Interest, Desire, Action). This study utilizes qualitative methods with a descriptive approach. Data collection techniques include observation, interviews, and documentation. Research informants consist of BPRS Amanah Bangsa marketing and consumers. The results show that at the attention stage, consumers can find out about products through the bank directly in the field, social media, pamphlets, and education provided. At the interest stage, consumers are interested because of the benefits and advantages. The desire stage is achieved through strengthening confidence in the security of deposits, clearly the transparency of information on the institution's performance, friendly service, and real testimonials from other users. At the action stage, consumers show their decisions because they have been convinced from the start. This encouragement is influenced by repeated persuasive approaches, easy account opening, and savings with prizes. Each stage illustrates that each consumer does not spontaneously show their interest, but develops gradually due to their beliefs and perceptions from what they see, receive, and feel directly.